Coinfection with Canine Distemper Virus and Yellow Fever Virus in a Neotropical Primate in Brazil - Maria Angélica Monteiro de Mello Mares-Guia; Marina Carvalho Furtado; Flávia Löwen Levy Chalhoub; Maria Dulce Portugal; Janice Mery Chicarino de Oliveira Coelho; Ana Maria Bispo de Filippis; Felipe Gomes Naveca (Viruses)
We describe a natural coinfection with canine distemper virus (CDV) and yellow fever virus in a free-ranging neotropical primate of the genus Callithrix, found dead in the northeastern region of Brazil. The laboratory diagnosis included histopathology, immunohistochemistry, rRT-PCR, and phylogenetic analyses. The CDV sequences from this primate in Brazil represent a divergent lineage in Rio Grande do Norte, closely related to genotypes EU1/South America 1 and South America 2. To our knowledge, this is the first report of natural coinfection by CDV and yellow fever virus in a neotropical primate, underscoring the need to further investigate the circulation of this virus in Brazilian nonhuman primates and its potential implications for wildlife conservation.